Optimalisasi Pelayanan dan Manajemen SDM di UPT Pengelolaan Pendapatan Bagan Batu, Bapenda Provinsi Riau - Safitri, Kenanga; Rahmani, Ahmadi Bi (Innovative: Journal Of Social Science Research, 2024)
The Revenue Management Technology Implementation Unit (UPT) Bagan Batu with the support of the Riau Regional Revenue Agency (Bapenda) has a strategic role. As one of the authorities tasked with managing regional revenue sources, the UPT is tasked with optimizing the collection of taxes, import duties, and other legitimate sources of revenue. Given the complexity of these tasks, aspects of public service and human resources (HR) are the keys to operational success. The purpose of this article is to determine the technical services and human resource management at the Bagan Batu Revenue Management UPT. This study uses a qualitative approach with the aim of deeply understanding the technical services and human resource management (HR) at the Bagan Batu Revenue Management UPT, Riau Province Regional Revenue Agency (Bapenda). Human resource management (HR) and public services at the Bagan Batu Revenue Management UPT have a strategic role in supporting the optimization of regional revenue. Effective and efficient services are supported by information technology and good HR governance.